Case report: The altered rate of monocytic cell death in a patient of Muckle-Wells syndrome with atypical clinical course - Murakawa, Saori; Yoneda, Toru; Hoshina, Takayuki; Ishimura, Masataka; Kusuhara, Koichi (Frontiers in Pediatrics, 2023)
Muckle-Wells syndrome (MWS) is an autosomal dominant autoinflammatory disease recognized as the intermediate phenotype of cryopyrin-associated periodic syndrome (CAPS) caused by NLRP3 gene mutation. It often takes a long time before the diagnosis is made because the clinical presentation of MWS is variable. We report a pediatric case who had had persistently elevated serum C-reactive protein (CRP) level since infancy and was diagnosed with MWS by the development of sensorineural hearing loss in school age. The patient had no periodic symptoms of MWS until the development of sensorineural hearing loss. It is important to differentiate MWS in patients with persistent serum CRP elevation, even if no periodic symptoms, including fever, arthralgia, myalgia and rash, are observed. Furthermore, in this patient, lipopolysaccharide (LPS)-induced monocytic cell death occurred, but to a lesser degree than has been reported in patients with chronic infantile neurological cutaneous, and articular syndrome (CINCA). Because CINCA and MWS are phenotypic variants on the same clinical spectrum, this suggests that a further large-scale study is desired to investigate the association between degree of monocytic cell death and disease severity in CAPS patients.